Diseño de una máquina para un proceso de triturado de heces de gallina. - Darwin Xavier, Colimba Tamba. (2021)
The objective of this titling project was to design a machine for grinding chicken feces to achieve a more homogeneous product and to improve its use as fertilizer at the ¨La Rosa¨ Farm. As a starting point for the design of the equipment, the production capacity of the farm for this product was considered on a monthly basis, which is 2700 kg (54 qq per month). The best performance crusher alternative for this project is a toothed roller type crusher, which is composed of a driving roller and a driven roller, which consist of 15 knives and 15 counter blades of 6 edges each, located in the crushing area with an operating capacity of 1.57 cubic meters. Additionally, in the power transmission it was essential to assemble a flexible mechanical coupling (double), which provides a greater degree of eccentricity, avoiding mechanical phenomena such as unbalance, decalibration or collision. To validate this proposal, a CAD computational tool was used that allowed the design of each of the mechanical elements of the machine and a CAE for the analysis of finite elements, where the behavior of each of the designed mechanical elements was demonstrated, which were: motor tree -driven, blades, gears and structure. Finally, the selection of the motor and the control part for turning the equipment on and off was made.